2008
DOI: 10.1590/s1516-93322008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Uso do óleo de pequi (Caryocar brasiliense) em emulsões cosméticas: desenvolvimento e avaliação da estabilidade física

Abstract: Os objetivos deste trabalho foram desenvolver e avaliar a estabilidade física de emulsões O/A contendo óleo de pequi (Caryocar brasiliense). Emulsões O/A contendo 10,0% (p/p) de INTRODUÇÃOEmulsão é um sistema termodinamicamente instável resultante da mistura de dois líquidos imiscíveis entre si e uma terceira fase contendo agente emulsificante (Breuer, 1985).De acordo com a natureza da fase externa, contínua ou ainda conhecida como dispersante podem ser classificadas em: emulsão água em óleo (A/O) a que contém… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
25

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 24 publications
0
23
0
25
Order By: Relevance
“…Pianovski [64], cites buriti as one of the main sources of pro-vitamin A found in Brazilian biodiversity. In the present study, the total weight of the pulp of the buriti was 62.93%, 8.25% of total carbohydrates, 5.17% of these total dietary fibres, 2.10% of the protein with predominance of amino acids Sulphur and tryptophan.…”
Section: Buriti (Mauritia Flexuosa L) General Characteristics Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…Pianovski [64], cites buriti as one of the main sources of pro-vitamin A found in Brazilian biodiversity. In the present study, the total weight of the pulp of the buriti was 62.93%, 8.25% of total carbohydrates, 5.17% of these total dietary fibres, 2.10% of the protein with predominance of amino acids Sulphur and tryptophan.…”
Section: Buriti (Mauritia Flexuosa L) General Characteristics Of Thementioning
confidence: 99%
“…This fruit also offers high nutritional value when compared to other fruits. According to Pianovski [64], buriti pulp has levels of B vitamins (B1, B2 and PP) equivalent to or higher than other fruits such as avocado, banana and guava, reported that the fruit has some minerals in important amounts, such as calcium, iron and selenium [63][64][65][66]. …”
Section: Buriti (Mauritia Flexuosa L) General Characteristics Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Due to its differentiated flavour and oil content, the souari fruit can be exploited for the preparation of various products such as the manufacture of flour and liquors from the souari pulp and cosmetics, soaps and spices from the oil (PIANOVSKI et al, 2008;OLIVEIRA et al, 2008;SOUZA et al, 2014). One way to facilitate the spread of the souari on the market involves the development of a bouillon cube as proposed by Barbosa et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have recognized the great potential of the pequi pulp oil for the production of cosmetics (PIANOVSKI et al, 2008). Furthermore, due to the low level of polyunsaturated fatty acids and high concentration of monounsaturated acid, this oil can be used in processes that involve frying and cooking (LOLOS; OREOPOULOU; TZIA, 1999;SEGALL et al, 2006).…”
Section: Introductionmentioning
confidence: 99%